Procedure for deformation detection using visual metrology - Ibrahim, Mohd. Sharuddin (2004)
Deformation detection via visual metrology (geodetic method) for inspection and data validity of an object has high potential in structure measurement. Visual metrology are based on close range photogrammetry i.e. V-STARS system. The V-STARS system is an enhanced (and portable) digital close range photogrammetric system for precise 3D coordinate measurement using special high-resolution digital intelligent camera (INCA), special target (high contras retro-reflective) and special software, for the automation of the entire measurement process. The typically accuracy of V-STARS is better than 10 ppm, i.e. about 0.010mm on a 1.0m object. This research focuses on the procedure and potential of deformation detection using visual metrology technique and S-transformation for geometrical analysis via displacement vector and graphic presentation. A simulation test is included to verify the practicality of the procedure.